A Study of Kindergarten 2 Students’ English Phonics Achievement and Their Perceptions towards the Use of English Phonics Online Games at St. Mark’s International School, Thailand - Parreno, Maria Donna Aguilar; Eamoraphan, Suwattana (Scholar: Human Sciences, 2017)
This study aimed to compare the Kindergarten 2 students’ achievement in English Phonics before and after the use of English Phonics online games and to find out their perceptions towards such games. Eleven Kindergarten 2 students of St. Mark’s International School in the academic year 2015-2016 participated in the two-month study. This research used a mixed method design. A one-group pretest-posttest experiment was conducted to determine if there was a significant difference in the students’ English Phonics achievement before and after using English Phonics online games. In addition, an interview on how the students’ perceived the use of English Phonics online games was done. Analyses showed that Kindergarten 2 students’ English Phonics achievement was very good before the use of online games, and it increased to excellent after the use of online games. Paired Samples t-test revealed that there was a significant difference between the pre- and post-tests scores of Kindergarten 2 students before and after using English Phonics online games at the level of 0.05. The interview results revealed that: 1) all Kindergarten 2 students had positive perceptions towards the use of online games in English Phonics; 2) the students had positive perceptions towards the use of English phonics online games because the games helped them learn how to spell and read and featured animations, colorful and attractive common objects, and interactive/hands-on and game/challenge components. Based on the findings, the use of online games in English Phonics is recommended in teaching and learning English Phonics, especially for young learners. Further relevant studies are also recommended.